The Role of Savings and Loan Cooperatives in MSME Development Efforts at KSPPS BTM Perkasa Purbalingga - Sevita Sari Dewi; Suci Indah Pratiwi; Adi Wiratno (CV. Ulil Albab Corp, 2024)
Saving and Loan Cooperatives (KSPs) have become one of the main pillars in supporting the development of Micro, Small and Medium Enterprises (MSMEs) in various countries. This article analyzes the important role of KSPs in MSME development efforts, particularly in the context of KSPPS BTM Perkasa Purbalingga. This research uses descriptive qualitative methods with in-depth interviews and participatory observation to collect data from KSP members and management of KSPPS BTM Perkasa Purbalingga. The results show that KSP has a strategic role in providing access to capital, business assistance, and strengthening networks and collaboration for MSMEs. KSPPS BTM Perkasa Purbalingga has particulary succeeded in improving MSMEs' access to capital with affordable and flexible loan services. In addition, the assistance provided by KSP helps MSMEs to manage their businesses more effectively and efficiently. The active involvement of members in KSP activities also strengthens solidarity and mutual support among MSMEs. Collaboration between MSMEs in the form of joint product development or joint marketing has improved the competitiveness and market penetration of local MSMEs. This article concludes that KSPs, especially KSPPS BTM Perkasa Purbalingga, have a significant role in supporting the growth and development of MSMEs. The implication of this research is the need to continue to encourage the development of KSPs as well as strengthen cooperation between KSPs and MSMEs to create an inclusive and sustainable business ecosystem.